2021
DOI: 10.3390/molecules26175138
|View full text |Cite
|
Sign up to set email alerts
|

Phages and Enzybiotics in Food Biopreservation

Abstract: Presently, biopreservation through protective bacterial cultures and their antimicrobial products or using antibacterial compounds derived from plants are proposed as feasible strategies to maintain the long shelf-life of products. Another emerging category of food biopreservatives are bacteriophages or their antibacterial enzymes called “phage lysins” or “enzybiotics”, which can be used directly as antibacterial agents due to their ability to act on the membranes of bacteria and destroy them. Bacteriophages a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 235 publications
0
10
0
Order By: Relevance
“…An example of this would be the endolysins, a remarkably diverse group of catalytic enzymes that degrade the cell wall of the host so that the phage progeny can escape ( 26 ). In recent years, these proteins have awakened increased interest for their potential to be used as antimicrobial agents ( 27 , 28 ). Culture-free approaches have been applied to great effect in order to broaden the diversity of endolysins.…”
Section: Resultsmentioning
confidence: 99%
“…An example of this would be the endolysins, a remarkably diverse group of catalytic enzymes that degrade the cell wall of the host so that the phage progeny can escape ( 26 ). In recent years, these proteins have awakened increased interest for their potential to be used as antimicrobial agents ( 27 , 28 ). Culture-free approaches have been applied to great effect in order to broaden the diversity of endolysins.…”
Section: Resultsmentioning
confidence: 99%
“…There are several advantages to using phages over chemical antibacterial agents, including the fact that they do not contribute to deterioration of the product's quality; that they may be applied to a wide range of substrates; and that resistance to viruses can be addressed much more simply, in comparison to commonly used antibacterial agents [66][67][68]. It has been found that phages can naturally be found in food, which indicates that this is one way for them to come into contact with humans [69]. In addition to being cost-effective and easy to use, phage-based techniques are establishing themselves as an alternative to traditional antibacterial treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, this formulation is being investigated for safety and efficacy of a single intravenous dose of N-Rephasin ® SAL200 for persistent S. aureus bacteremia under phase IIa clinical study [ 243 ]. Considering the efficacy of phages and phage-derived lysins, the USFDA has approved the application of bacteriophage-based products as an eco-friendly approach for the control of food borne pathogens [ 240 , 244 ]. Further, phage-derived lytic proteins possess several advantages over antibiotics, namely: (a) rapid and extensive bactericidal action against the target pathogen, (b) lack of resistance development due to their specific action on conserved structural components of bacteria, (c) synergistic action with other lysins or antibiotics, and (d) their effect on phenotypically resistant persister cells growing on mucosal surfaces or in biofilms [ 245 ].…”
Section: Strategies Targeting Antimicrobial-resistant Bacteriamentioning
confidence: 99%